Non-Invasive Diagnostic Test for Advanced Fibrosis in Adolescents With Non-Alcoholic Fatty Liver Disease - Antonella Mosca; Luca Della Volpe; Anna Alisi; Silvio Veraldi; Paola Francalanci; Giuseppe Maggiore (Frontiers Media S.A., 2022)
IntroductionNon-alcoholic fatty liver disease (NAFLD) is a multifaceted disease that includes a wide spectrum of liver damage. The presence and the degree of fibrosis are considered important factors for the prognosis of NAFLD and in predicting the risk of developing cirrhosis. Our aim was to evaluate the usefulness of four fibrosis scores (aspartate aminotransferase/Platelet Index [APRI], FIB-4, NAFLD Fibrosis Score [NFS], and Hepamet) in predicting different degrees of fibrosis among children with biopsy-proven NAFLD.MethodsAbout 286 adolescents [mean age 14.3 years ± 2.5; 154 (53.6%) males], referred between January 2014 and December 2019, with biopsy-proven NAFLD were enrolled.ResultsAbout 173 (60.4%) patients presented fibrosis at histological analysis. In particular: 140 (49.3%) patients had F = 1, 31 (10.8%), had F = 2 and 2 (0.66%) had F = 3. APRI (AUROC 0.619, 95% CI 0.556-0.679) and Hepamet (AUROC 0.778, 95% CI 0.722-0.828) scores had significant (p < 0.001) accuracy to distinguish subjects with fibrosis; while NFS and FIB-4 had not. APRI had a positive predictive value (PPV) of 62.77% (95% CI 57.96-67.35) and an negative predictive value (NPV) of 52.01% (95% CI 46.54-57.43); Hepamet a PPV of 63.24% (95% CI 59.95-66.41) and an NPV of 61.29% (52.9-69.01).ConclusionsOur study showed that Hepamet and APRI perform better than NFS and FIB-4 for identifying fibrosis in patients with NAFLD, but do not have PPVs so high to be considered diagnostic. Therefore, they cannot be employed, in children, for a certain diagnosis of fibrosis or its progression and cannot replace liver biopsy as the gold diagnostic standard. It is, therefore, necessary to continue to research and develop new markers of exclusive fibrosis.